Randomly stopped minima and maxima with exponential-type distributions - Ragulina, Olena; Šiaulys, Jonas (Nonlinear Analysis: Modelling and Control, 2019)
Let {ξ1, ξ2,...} be a sequence of independent real-valued and possibly nonidentically distributed random variables. Suppose that η is a nonnegative, nondegenerate at 0 and integer-valued random variable, which is independent of {ξ1, ξ2,...}. In this paper, we consider conditions for {ξ1, ξ2,...} and η under which the distributions of the randomly stopped maxima and minima as well as randomly stopped maxima of sums and randomly stopped minima of sums belong to the class of exponential distributions.
Keywords: class of exponential distributions; counting random variable; randomly stopped maxima; randomly stopped minima; maximum of sums; minimum of sums; closure property